Focus on peripherally inserted central catheters in critically ill patients - Cotogni, Paolo (World J Crit Care Med, 2014)
Venous access devices are of pivotal importance for an increasing number of critically ill patients in a variety of disease states and in a variety of clinical settings (emergency, intensive care, surgery) and for different purposes (fluids or drugs infusions, parenteral nutrition, antibiotic therapy, hemodynamic monitoring, procedures of dialysis/apheresis). However, healthcare professionals are commonly worried about the possible consequences that may result using a central venous access device (CVAD) (mainly, bloodstream infections and thrombosis), both peripherally inserted central catheters (PICCs) and centrally inserted central catheters (CICCs). This review aims to discuss indications, insertion techniques, and care of PICCs in critically ill patients. PICCs have many advantages over standard CICCs. First of all, their insertion is easy and safe -due to their placement into peripheral veins of the arm- and the advantage of a central location of catheter tip suitable for all osmolarity and pH solutions. Using the ultrasound-guidance for the PICC insertion, the risk of hemothorax and pneumothorax can be avoided, as well as the possibility of primary malposition is very low. PICC placement is also appropriate to avoid post-procedural hemorrhage in patients with an abnormal coagulative state who need a CVAD. Some limits previously ascribed to PICCs (i.e., low flow rates, difficult central venous pressure monitoring, lack of safety for radio-diagnostic procedures, single-lumen) have delayed their start up in the intensive care units as common practice. Though, the recent development of power-injectable PICCs overcomes these technical limitations and PICCs have started to spread in critical care settings. Two important take-home messages may be drawn from this review. First, the incidence of complications varies depending on venous accesses and healthcare professionals should be aware of the different clinical performance as well as of the different risks associated with each type of CVAD (CICCs or PICCs). Second, an inappropriate CVAD choice and, particularly, an inadequate insertion technique are relevant-and often not recognized-potential risk factors for complications in critically ill patients. We strongly believe that all healthcare professionals involved in the choice, insertion or management of CVADs in critically ill patients should know all potential risk factors of complications. This knowledge may minimize complications and guarantee longevity to the CVAD optimizing the risk/benefit ratio of CVAD insertion and use. Proper management of CVADs in critical care saves lines and lives. Much evidence from the medical literature and from the clinical practice supports our belief that, compared to CICCs, the so-called power-injectable peripherally inserted central catheters are a good alternative choice in critical care.